Treatments for Cervical Spondylosis with Acupuncture and Tuina Massage - ศิริธีราฐิติกุล ปุณยภัสร์ (Journal of Health Science of Thailand, 2022)
Cervical spondylosis is caused by deterioration of the discs and joints in the cervical spine and is a common disease among the elderly. Since it is a bone and joint disorder, there is no cure for it. The most common treatment for cervical spondylosis is symptomatic treatment with painkillers and steroid injections, or even surgery. By relevant research article search in various databases such as CNKI, google scholar, PubMed, science direct, this research is a systematic review of the literature for knowledge collection related to cervical spondylosis treatment with acupuncture and Tuina massage. The research articles were published in 2014 to 2020 and in domestic and international journals. The specifying key words in Thai, Chinese, and English language searches were as follows: cervical spondylosis, acupuncture, Tuina, traditional chinese medicine. Here the results showed that a total of 17 trials met the inclusion criteria and all were randomized controlled trials (RCTs) with the control groups. Based on the treatment methods, the treatment divided into 3 ways as follows: treatment of cervical spondylosis with acupuncture 6 articles, followed by treatment of cervical spondylosis with Tuina massage, and treatment of cervical spondylosis with both acupuncture and Tuina massage were 5, and 6 articles, respectively. Most of them were research, which was experiments originated from China and was published in China database CNKI. Based on content analysis to describe the effects of acupuncture and Tuina massage, patients with cervical spondylosis had lower pain levels. Also, they had increasing degrees of neck movement in all directions and had an increasing quality of life. According to laboratory analysis, indicators of blood flow have improved. As a results, the treatment of cervical spondylosis with acupuncture and Tuina massage is an alternative way for these patients. It is also a dissemination of guidelines for treating cervical osteoarthritis with alternative medicine in Thailand and leads to the development of a safe and sustainable treatment for cervical spondylosis.